HUBUNGAN ANTARA DUKUNGAN SOSIAL DAN EMOTION FOCUSED COPING PADA PENDERITA STROKE DI KLINIK X KEDIRI - Putri, Junike (EXPERIENTIA : Jurnal Psikologi Indonesia, 2019)
This study is to find out whether there is a relationship between social support and emotion focused coping on stroke patients in X clinic at Kediri city. Emotion focused coping is something that involves efforts to manage emotions caused by stressful events. Social support refers to a comfort, attention, self-esteem or assistance available from the group for individuals. This study used a quantitative approach with correlational techniques. Research subjects numbered 106 patients who had a stroke in Kediri, with paralysis of some parts of the body and aged 40-65 years. This study using purposive sampling. The data in this study were obtained using social support scale and emotion focused coping scale. The data analysis technique used a non parametric kendall tau-b. The results showed there was no relationship between social support and emotion focused coping, with a sig value = 0.097 (p> 0.05). This happens because there are several other factors that are more related to emotion focused coping, such as the type of problem, age and gender. In addition, based on the results of observations and interviews in the field, the researcher found and indicated that there is a possibility of a lack of attachment between family members, which causes the support provided has no impact on stroke patients.